Evaporation-free inverted organic photovoltaics using a mixture of silver nanoparticle ink formulations for solution-processed top electrodes - Georgiou, Efthymios; Savva, Achilleas; Neophytou, Marios; Hermerschmidt, Felix; Demosthenous, Tasos; Choulis, Stelios A. (My University, 2014)
We report an investigation of inkjet-printed silver (Ag) nanoparticle inks combined with a poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) formulation for solution-processed top electrodes in inverted organic photovoltaics (OPVs) employing the poly(3-hexylthiopehene):phenyl-C61-butyric acid methyl ester material system. We propose a suitable mixture of Ag nanoparticle inks to control the printability and electrical conductivity of the solution-processed top electrode. Based on the proposed solution-processed hole-selective contact, a power conversion efficiency in the range of 3% is reported for evaporation-free inverted OPVs.
Keywords: Polymer solar-cells; Back electrodes; Layer; Conductivity; Degradation